New business models for Cultural Institutions = Nowe modele biznesowe dla instytucji kultury - Nikiel, Sławomir (Zielona Góra: Faculty of Economics and Management Press)
Total integration of social media and internet into daily life of the young people is the most distinct demographic characteristics of the Generation Z (born between 1995 and 2015). For Cultural and Creative Industries and Institutions in order to engage with this audience efficiently, their business models have to consider social media and more participative approach.
Keywords: administracja; zarządzanie; instytucje kultury; przemysły kreatywne; model biznesowy; business administration; management; cultural institutions; CCII; business models